Effect of Sex on Hematological Profile of Zovawk - An Indigenous Pig of Mizoram Hills - Mayengbam, Prava; Tolenkhomba, Thingujam Chaa (Indian Journal of Hill Farming, 2018)
Hematological profile was investigated in three different age groups of Zovawk viz. pre-weaning (4 to 5 weeks old), grower (24 to 26 weeks old) and adults (14 to 16 months old) in three different phases of a year. Each of the groups consisted of 36 pigs with equal number of male and female. A total of 324 blood samples collected from different groups was investigated to find out the effect of sex on total erythrocyte count (TEC), hemoglobin (Hb), total leukocyte count (TLC), packed cell volume (PCV), mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and differential leucocyte count (DLC) for lymphocyte, Neutrophil, monocyte, eosinophil and basophil by using automatic blood analyzer Vetscan HM5. Influence of sex on hematological profile was found only in pre-weaning group. Out of all the hematological parameters investigated, sex influenced TEC (P